The Extension of Maggot as a High-Protein Chicken Feed for Latompe Farming Community - La Ode Abdul Asis Hasidu; Thamrin; Wa Ode Amrina (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
This service program aims to provide an alternative feed for local chickens (Gallus domesticus) with high protein to the Latompe farming community. The alternative feed are maggots which are the larvae of Black Soldier Flies (Hermetia illucens). It is hoped that the chicken farmers in Latompe village will no longer only depend on carbohydrate-based feed such as corn to obtain maximum chicken growth. To transfer that new technology, the farmer's educators managed a mass socialization and made presentation slides, leaflets, and on-site practice followed by periodic assistance. As a result, the maggot extension program has been running well and several breeders have been able to cultivate maggots for their chickens' feed. It is hoped that this program can be implemented sustainably to obtain maximum production of local chickens.